Superactivity and dual reactivity of the system N-iodosuccinimide-H 2SO4 in the iodination of deactivated arenes; Russian Journal of Organic Chemistry; Vol. 43, iss. 9 - Chaikovskii V. K. Vitold Kazimirovich; Filimonov V. D. Viktor Dmitrievich; Skorokhodov V. I.; Ogorodnikov V. D. (2007, 2007)
Title screen